Combination of Trans-Resveratrol and ε-Viniferin Induces a Hepatoprotective Effect in Rats with Severe Acute Liver Failure via Reduction of Oxidative Stress and MMP-9 Expression - João C. Fernandes (MDPI AG, 2021)
Stilbenes are a major grapevine class of phenolic compounds, known for their biological activities, including anti-inflammatory and antioxidant, but never studied in combination. We aimed to evaluate the effect of trans-resveratrol + ε-viniferin as an antioxidant mixture and its role in inflammatory development an in vivo model of severe acute liver failure induced with TAA. Trans-resveratrol + trans-ε-viniferin (5 mg/kg each) was administered to Wistar rats. Resveratrol + ε-viniferin significantly decreased TBARS and SOD activity and restored CAT and GST activities in the treated group. This stilbene combination reduced the expression of TNFα, iNOS, and COX-2, and inhibited MMP-9. The combination of resveratrol + ε-viniferin had a hepatoprotective effect, reducing DNA damage, exhibiting a protective role on the antioxidant pathway by altering SOD, CAT, and GST activities; by downregulating TNFα, COX-2, and iNOS; and upregulating IL-10. Our results suggested that adding viniferin to resveratrol may be more effective in hepatoprotection than resveratrol alone, opening a new perspective on using this stilbene combination in functional diets.